Kebijakan Deviden, Perputaran Persediaan Dan Perputaran Modal Kerja, Kebijakan Hutang dan Set Kesempatan Investasi - Dewi, Putu Purnama; Lila Man, Helfrida (E-Jurnal Akuntansi; Vol 26 No 3 (2019), 2019)
This study aims to exmine the effect of inventory turnover dividend policy and working capital turnover on debt policy with the investment opportunity set as a moderating variable in manufacturing companies of various industrialsectors listed on the Indonesia Stock Exchange for the period 2015 to 2017. This research uses purposive sampling method that is determining the number of samples taken randomly basedon certain criteria The eligible sample is 10 companies in the various industrial sector listed. Analysis data using multiple regression techniques. Keywords: Dividend policy, inventory turnover, working capital turnover, investment opportunity set, debt policy .